2015
DOI: 10.1016/j.buildenv.2015.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the aerosol infiltration characteristics in a cultural heritage building: The Baroque Library Hall in Prague

Abstract: Please cite this article as: Chatoutsidou SE, Mašková L, Ondráčková L, Ondráček J, Lazaridis M, Smolík J, Modeling of the aerosol infiltration characteristics in a cultural heritage building: The Baroque Library Hall in Prague, Building and Environment (2015), doi: 10.1016/j.buildenv.2015 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 53 publications
(88 reference statements)
3
18
0
Order By: Relevance
“…The average value a = 0.13 h -1 was stable with the relative standard deviation (RSD) approximately 14%. The same average value was found in spring campaign in 2009 (Chatoutsidou et al, 2015).…”
Section: Estimation Of Ventilation Ratesupporting
confidence: 86%
See 4 more Smart Citations
“…The average value a = 0.13 h -1 was stable with the relative standard deviation (RSD) approximately 14%. The same average value was found in spring campaign in 2009 (Chatoutsidou et al, 2015).…”
Section: Estimation Of Ventilation Ratesupporting
confidence: 86%
“…Temporal variation of size resolved indoor and outdoor PM showed that main source of indoor coarse PM are visitors and fine PM infiltration from the outdoor environment (Chatoutsidou et al, 2015). Similar effect has been already described in several studies related to indoor air quality in museums (e.g., Camuffo et al, 1999;Worobiec et al, 2008;Wang et al, 2015;Xiu et al, 2015).…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations